Toxic Ingestion/Acute Tricyclic Antidepressant (TCA) Ingestion - Bryan Beaver; Mary Wittler (Association of American Medical Colleges, 2015)
Abstract Introduction Acute tricyclic antidepressant (TCA) overdose is an uncommon but life threatening ingestion. The purpose of this simulation is to present an acute TCA overdose case that allows medical students, emergency medicine residents, and pediatric emergency medicine fellows to test their knowledge base and critically evaluate the management of this type of ingestion. Methods This simulation contains four elements. The first element is the case narrative, which includes all pertinent case information, interpretations of the case information, and anticipated case branch points. The second element is a PowerPoint presentation that contains pertinent case lab information, x-ray, and EKG data to be used during the case simulation. The third element is a PowerPoint containing teaching points for the debriefing session. Finally, an evaluation form is included that provides recommended care actions. Results This case has been used numerous times for group simulation training; additionally, the case content has been used more than 15 times as an oral board type case. Feedback on the case scenario occurred during each of these uses. The combination of participation in the simulation scenario, interactive feedback session that focused on debriefing questions, and review of the brief PowerPoint lecture addressed all of the listed objectives for the learners. The case was definitely effective in teaching management of TCA ingestion. Additionally, most of the participants identified a general lack of comfort in managing this ingestion (even when the management decisions were correct), secondary to lack of familiarity, as this is an uncommon ingestion. In this regard, the case was received well by participants, as it is an opportunity to critically think through, and review, the management decisions. Discussion This case successfully teaches medical students, emergency medicine residents, and pediatric emergency medicine fellows critical aspects to the evaluation and management of a TCA overdose. A group simulation case scenario was chosen to promote clinical decision making and to critically evaluate those management decisions.